Labour Force Participation of Women in Malaysia (Jurnal Pembangunan Sosial, 2010)
This article analyses the women labor force participation in Malaysia. The rapid absorption of women into the labor market has been influenced by several factors. The rapid economic growth was due largely to important growth inthe manufacturing and services sectors, where substantial and proportionally larger increase of female workers has been registered. Among all sectors of the economy, the manufacturing sector has recorded the highest growth rate during the last decade. The rising in the female labor force participation may also be attributable to improving economic incentives in employment and policies favoring the employment of women. In addition, the combined effects of the increase in years of schooling, access to family planning services, improved maternal and availability of child care, leading to arise in the average age at marriage, have allowed women to take advantage of the increased employment opportunities.